China, Inc. : how the rise of the next superpower challenges America and the world - Fishman, Ted C., 1958- (New York : Scribner, 2005)
Draws on interviews with Chinese, American, and European businesspeople to predict economic challenges as a result of China's growing ability to produce U.S. products more cheaply, and to draw conclusions about China's future as a superpower.
The world shrinks as China grows -- Taking a slow boat in a fast China -- The revolution against the Communist revolution -- To make 16 billion socks, first break the law -- Meet George Jetson, in Beijing -- Chairman Mao sells soup -- Through the looking glass -- The China price -- How the race to the bottom is a race to the top -- Pirate nation -- The Chinese-American economy -- The Chinese century -- One last story.
Includes bibliographical references (p. 321-324) and index.
Keywords: Industrialization -- China; Investments, Foreign -- China; Competition, International; China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; China -- Foreign economic relations -- United States; United States -- Foreign economic relations -- China